Prior Knowledge and Entrepreneurial Discovery: A Classroom Methodology for Idea Generation - Nixon, Robert; Bishop, Karen; Clouse, Van G.H; Kemelgor, Bruce (Senate Hall, 2006)
The consideration-set search method used assumes that the value of wealth-generating opportunities is directly related to expertise in specific areas of an individual's prior knowledge. This paper pursues two objectives. First, we describe how the consideration-set method used in the original experiments was converted into five training sessions and delivered in an educational setting. Graduate students, engaged in an Opportunity Discovery course, participated in classroom training using the consideration-set search processes to discover opportunities with wealth-generating potential. Each individual recorded the opportunities discovered during the process in a personal Idea Journal. A knowledgeable panel scored each opportunity for potential wealth-generation based on the idea's value, rarity, imperfect imitability, and entrepreneurial fitness. We provide considerable details so that others may incorporate the training into their curriculum. Second, we briefly examine the results and effects of introducing this opportunity discovery method into an entrepreneurship education setting. Results indicate that about 7% of the opportunities discovered during the classroom experience had wealth-generating potential, suggesting that the consideration-set search methodology was translated, taught and applied effectively in an educational setting. We argue that using this methodology in an Opportunity Discovery course will enhance the quality of ideas discovered.
Keywords: entrepreneurship|education|discovery